2023
DOI: 10.3390/su15097108
|View full text |Cite
|
Sign up to set email alerts
|

Crisis Resilience of Startup Companies (The Case of Hungary among the Visegrad Countries with a Focus on the Pandemic)

Abstract: The study examines the crisis resilience of startup companies in Hungary among the Visegrad countries as a result of the pandemic situation. It aims to provide guidance on what support is needed for startups in the post-crisis period to re-launch the economy and to contribute to the region’s economy with positive results. The research was carried out in two stages: first, in 2021 through an online survey, and then, in 2022 in-depth interviews due to the economic crisis caused by COVID-19 and the Russian–Ukrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…The COVID-19 pandemic and resulting public health crisis had an enormous impact on the global economy at all scales and in all sectors, with disruptions affecting most types of economic activity [2][3][4][5][6][7][8][9][10][11][12], including related sectors such as logistics, transport, and energy [13][14][15][16]24]. While tourism and related activities, including food services, were most affected [20][21][22][23][24], agriculture was affected to varying degrees, depending on the scale, type, and nature of production and geographical location .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic and resulting public health crisis had an enormous impact on the global economy at all scales and in all sectors, with disruptions affecting most types of economic activity [2][3][4][5][6][7][8][9][10][11][12], including related sectors such as logistics, transport, and energy [13][14][15][16]24]. While tourism and related activities, including food services, were most affected [20][21][22][23][24], agriculture was affected to varying degrees, depending on the scale, type, and nature of production and geographical location .…”
Section: Discussionmentioning
confidence: 99%
“…A start-up was defined as "a rapidly growing firm due to its innovation in terms of products/services and processes through the aid of IT/ICT enabled services" [1] or as "a newly established company that is in the early stages of development and is focused on bringing an innovative product, service, or business model to the market" [2] recorded a split result with positive outcomes for IT, e-commerce, healthcare-related, and digital education. At the same time, hospitality and tourism were negatively impacted [3], as revealed in Hungary and the Visegrad Countries in Central Europe. Despite immediate policy measures to support start-ups during the pandemic, the crisis was a natural selection among the newly created companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Analyzing the creation of new start-ups in the Visegrad Group countries, Poland is the leader, followed by the Czech Republic, Hungary, and Slovakia [53][54][55]. The emergence of new enterprises means that the potential is directed towards new concepts that have a chance to revolutionize markets.…”
Section: Economic Situation Of Enterprisesmentioning
confidence: 99%
“…The emergence of new enterprises means that the potential is directed towards new concepts that have a chance to revolutionize markets. Therefore, bankruptcies and problems in industries can be viewed through the system of opportunities that appear in the environment and that are used for new ideas [55][56][57].…”
Section: Economic Situation Of Enterprisesmentioning
confidence: 99%
“…They found that entrepreneurial returns in V4 countries are 22% higher on average than the employee return [42]. Kézai-Kurucz (2023) examined resilience, which is essential for startups in the V4 countries, as a key to survival during the COVID-19 pandemic [43].…”
Section: Characteristics Of the Sme Sector Of The Visegrad Countriesmentioning
confidence: 99%